Thermoregulation of lightweight geopolymer composites as a sustainable alternative to cement using phase change material impregnated bio-polyurethane foam - Aydogmus, Ercan; Guler, Onur; Ustaoglu, Abid; Gencel, Osman; Sari, Ahmet; Memis, Selcuk; Memon, Shazim Ali (Elsevier, 2026)
The modern days construction sector faces growing pressure to adopt materials that are both energy-efficient and environmentally responsible. This research presents bio-polyurethane foam (PBF) carrier impregnated with polyethylene glycol (PEG) as novel building material. The resulting composite using PEG as phase change material (PCM) simultaneously tackles two building-related issues: reducing the carbon footprint associated with cement production and lowering the operational energy demand of buildings through passive thermal regulation. Test results showed that the melting point of PEG-impregnated PBF composites was found to be to be 22.3 degrees C while the melting enthalpy was recorded as 78.3 J/g. The developed composite provided a nighttime cooling of up to 10 degrees C compared with geopolymers without PCM. With a 28-day compressive strength of 22 MPa, the material is suitable for use in elements subjected to low-to-medium load levels, especially in non-load-bearing or secondary load-bearing applications such as residential slabs, floors, and non-load-bearing walls. These results suggest strong potential for use in partition walls, wall blocks, and insulation panels designed to moderate indoor temperature fluctuations in energy-efficient buildings.
Keywords: Phase Change Material; Biopolyurethane Foam; Polyethylene Glycol; Thermal Energy Storage: Geopolymer Concrete; Energy And Energy Efficiency